High Incidence of Gestational Trophoblastic Disease in a Third-Level University-Hospital, Italy: A Retrospective Cohort Study - Capobianco, Giampiero; Tinacci, Elettra; Saderi, Laura; Dessole, Francesco; Petrillo, Marco; Madonia, Massimo; Virdis, Giuseppe; Olivari, Alessandro; Santeufemia, Davide Adriano; Cossu, Antonio; Dessole, Salvatore; Sotgiu, Giovanni; et al. (Frontiers in Oncology, 2021)
Introduction: to assess incidence, prognosis and obstetric outcome of patients treated for gestational trophoblastic disease GTD in a twenty-year period. Methods: retrospective study. Results: Fifty-four cases of GTD: 46 (85.18%) cases of Hydatidiform mole (HM); 8 cases of Persistent Gestational Trophoblastic Neoplasia (GTN) (14.81%): 6/8 cases (75%) GTN not metastatic; 2/8 cases (25%) GTN metastatic. In both cases, the metastases occurred in the lungs. In 3 out of 8 GTN cases (37.5%) a histological picture of chori-ocarcinoma emerged. The incidence of GTD cases treated from 2000 to 2020 was 1.8 cases per 1000 deliv-eries and 1.3 cases per 1000 pregnancies. Of the 54 patients, 30 (55.56%) presented showed normal serum hCG levels without the need for chemotherapy. On the other hand, 24 patients (44.44%) developed a persis-tent trophoblastic disease and underwent adjuvant therapy. The negative prognostic factors that affected the risk of persistence of GTD were: serum hCG levels at diagnosis greater than 100,000 mUI/mL; characteristic "snow storm" finding at the ultrasound diagnosis; a slow regression of serum hCG levels during follow-up; the persistence of high serum hCG levels (especially if greater than 1000 mUI/mL one month after suction curettage) that was the main risk factor for resistance to first-line chemotherapy. There were 10 pregnancies in total fol-lowing treatment. Patients survival in our study was 100%. Discussion: Although GTD is a rare disease, its incidence was 1.3 cases per 1,000 pregnancies in Sardinia, Italy, higher if compared with mean national and worldwide incidence.